Polymers with alternating anthracene and phenylene building blocks linked by ethynylene and/or vinylene units: Studying structure‐properties‐relationships. Issue 1 (11th October 2016) - Boudiba, Sameh; Růžička, Aleš; Ulbricht, Christoph; Enengl, Sandra; Enengl, Christina; Gasiorowski, Jacek; Yumusak, Cigdem; Pokorná, Veronika; Výprachtický, Drahomír; Hingerl, Kurt; Zahn, Dietrich R. T.; Tinti, Francesca; et al.
ABSTRACT: Four conjugated polymers (P1 –P4 ) consisting of alternating anthracene‐9, 10‐diyl and 1, 4‐phenylene building blocks connected via ethynylene as well as vinylene (P1 andP2 ), ethynylene‐only (P3 ), and vinylene‐only (P4 ) moieties, respectively, were synthesized and studied. The phenylene units in all four polymers bear 2‐ethylhexyloxy side‐chains to promote good solubility. The three polymers with vinylene units (P1, P2, andP4 ) were prepared using the Horner–Wadsworth–Emmons reaction. For the synthesis of the arylene‐ethynylene polymerP3, the palladium‐catalyzed Sonogashira cross‐coupling reaction was used. The polymers were characterized by NMR, Fourier transform infrared spectroscopy, and Raman spectroscopy. Photophysical, absorption and photoluminescence, and electrochemical properties were studied. Spectroscopic ellipsometry measurements were performed to gain more insight on the optical properties. In addition, the transport properties were investigated using admittance spectroscopy. The bulk hole mobility and its dependence on the electric field were evaluated forP1 andP2 . © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 129–143 Abstract : Conjugated polymers (P1 –P4 ) consisting of alternating anthracene‐9, 10‐diyl and 1, 4‐phenylene building blocks connected via ethynylene as well as vinylene (P1 andP2 ), ethynylene‐only (P3 ), and vinylene‐only (P4 ) moieties were synthesized and characterized. The comparative study of photophysical (absorption and photoluminescence, spectroscopic ellipsometry), electrochemical, and transport properties of these polymers yields insight on the impact of the ethynylene and/or vinylene moieties on their properties.